High Expression MicroRNA-206 Inhibits the Growth of Tumor Cells in Human Malignant Fibrous Histiocytoma - Li, Dejian; Zhao, Kai; Zhao, Ziwen; Jiang, Bo; Gong, Xianxu; Zhang, Yan; Guo, Yingqi; Xiao, Han; Wang, Ye; Liu, Hui; Yi, Chengqing; Gu, Wenguang (Frontiers in Cell and Developmental Biology, 2021)
Background: Malignant fibrous histiocytoma (MFH) is a common type of soft tissue sarcoma and a serious threat to human health. MFH often relapses locally after the curettage is related to the residual cancer stem cells (CSCs). Currently, the dysregulation of microRNA (miRNA) has been found to be closely related to the recurrence of CSCs. However, whether dysregulations of miRNAs exist in MFH, CSCs remained unknown. Methods: In this study, miRNAs in MFH CSCs and MFH common cells were examined by gene probe. Then, target genes and their functions involved in the signal pathway were predicted by the relevant database. Finally, the miRNAs’ target regulatory network was constructed. Furthermore, the miRNAs and target genes were identified by quantitative polymerase chain reaction, whereas miRNA analogs and antagonists were transfected in tumor cells to investigate cell proliferation ability further. Results: Results showed that a total of 47 miRNAs were found, including 16 that were upregulated and 31 that were downregulated. The screened differential miRNA showed a different expression in the cell resistant strains compared with the control group. Quantitative polymerase chain reaction analysis confirmed that the relative abundance of seven miRNAs and four target genes varied significantly. The encouraging issue is that we found Hsa-miR-206 significantly inhibited MFH proliferative activity. Conclusion: Hsa-miR-206 played a key role in regulating MFH CSC properties that might be a representative marker and target for the diagnosis and treatment of MFH in the future.